2023
DOI: 10.31219/osf.io/upb7f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How the Predictors of Math Achievement Change over Time: A Longitudinal Machine Learning Approach

Rosa Ellen Lavelle-Hill,
Anne C. Frenzel,
Thomas Goetz
et al.

Abstract: Researchers have focused extensively on understanding the factors influencing students' academic achievement over time. However, existing longitudinal studies have often examined only a limited number of predictors at one time, leaving gaps in our knowledge about how these predictors collectively contribute to achievement beyond prior performance and how their impact evolves during students' development. To address this, we employed machine learning to analyze longitudinal survey data from 3,425 German seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Yet, while machine learning models are highly adept at dealing with time series data (e.g., Hochreiter and Schmidhuber (1997); Tuli et al (2022)), there are limited approaches optimized for data with low T 10 . Instead, the problem is typically converted to a more traditional machine learning problem, for instance, by treating each time point as a different prediction problem (e.g., see Lavelle-Hill et al (2023b) Another challenge is that, by heavily relying on subjective self-reported data, many measurements in psychology research are deemed ordinal (e.g., Likert scales). In traditional statistics, while researchers typically analyze such data as continuous, models have nonetheless been developed to model this data type (i.e., ordinal regression (Bürkner and Vuorre, 2019)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, while machine learning models are highly adept at dealing with time series data (e.g., Hochreiter and Schmidhuber (1997); Tuli et al (2022)), there are limited approaches optimized for data with low T 10 . Instead, the problem is typically converted to a more traditional machine learning problem, for instance, by treating each time point as a different prediction problem (e.g., see Lavelle-Hill et al (2023b) Another challenge is that, by heavily relying on subjective self-reported data, many measurements in psychology research are deemed ordinal (e.g., Likert scales). In traditional statistics, while researchers typically analyze such data as continuous, models have nonetheless been developed to model this data type (i.e., ordinal regression (Bürkner and Vuorre, 2019)).…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning methods are seen as an appropriate tool to analyze large (and often unstructured) data (Faraway and Augustin, 2018). These methods can find complex (e.g., non-linear) patterns in data and have enabled accurate predictions of a number of different behaviors, for example, suicide attempts (Walsh et al, 2017); environmental behaviors (Lavelle-Hill et al, 2020), life outcomes (e.g., education achievement (Lavelle-Hill et al, 2023b); marital hardship (Salganik et al, 2020)), psychological constructs (e.g., personality traits (Youyou et al, 2015;Stachl et al, 2020)), developmental trajectories (Van Lissa et al, 2023;Van Lissa, 2022), clinical diagnoses (e.g., Alzheimer's disease (Lei et al, 2022)) as well as treatment outcomes (Chekroud et al, 2016). Contrary to the traditional statistical approach, which usually focuses on a single theoretically formalized statistical model, (supervised) machine learning follows an "algorithmic modeling" approach (Breiman, 2001b), which makes no assumptions about the underlying data generating mechanism, and seeks to find the function that best predicts the outcome from a set of possible predictors.…”
mentioning
confidence: 99%
See 1 more Smart Citation